Meditation and Its Regulatory Role on Sleep - Nagendra, Ravindra P.; Maruthai, Nirmala; Kutty, Bindu M. (Frontiers in Neurology, 2012)
Intense meditation practices help to achieve a harmony between body and mind. Meditation practices influence brain functions, induce various intrinsic neural plasticity events, modulate autonomic, metabolic, endocrine and immune functions and thus mediate global regulatory changes in various behavioural states including sleep. This brief review focuses on the effect of meditation as a self regulatory phenomenon on sleep.